Političnogeografske podlage čezmejne komunikacije na območju tromeje med Slovenijo, Italijo in Avstrijo - Bufon, Milan (Geografski vestnik, 2000)
The article deals with some political geographical aspects of cross-border communication in the three-border area between Slovenia, Italy and Austria. Here, a special transformation of an originally united territory in the frame of different state systems and in a peripheral condition may be observed. In spite of a common way of life in this Alpine environment, the investigated three-border area is facing cross-border communication and integration more as a potential than an actual situation. The reason for the above situation may be found in the very specificity of the Alpine human geography, where local communities were able to maintain their characteristics and an attitude of coexistence mainly because they preserved a modest level of mutual communication.
Keywords: politična geografija; obmejna območja; obmejno sodelovanje; regionalni razvoj; prostorski razvoj; tromeja; Slovenia; Slovenija; Italija; Italy; Austria; Avstrija